2007
DOI: 10.1007/s00467-006-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the use of mycophenolate mofetil in children with cyclosporine-dependent nephrotic syndrome

Abstract: Cyclosporine A (CsA) has relieved children with steroid-dependent nephrotic syndrome (NS) from steroid toxicity. However, most patients frequently relapse again when CsA is withdrawn, resulting in the development of CsA nephropathy for its long-term use. In order to assess the efficacy of mycophenolate mofetil (MMF) therapy, we prospectively analyzed 12 children with idiopathic steroid-dependent NS requiring long-term CsA therapy with MMF for at least 6 months. Mean follow-up after starting MMF was 11 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…The long-term treatment of children with CsA is effective but also has unfavourable side effects, of which hypertension and nephrotoxicity are the most important [6][7][8][9][10][11]. An alternative is welcome, and recent studies suggest a positive effect of MMF in children with nephrotic syndrome of various etiologies [12][13][14][15][16][17][18][19][20][21]. Here we report the first randomized controlled trial comparing the side effects and efficacy of MMF and CsA in children with frequently relapsing nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term treatment of children with CsA is effective but also has unfavourable side effects, of which hypertension and nephrotoxicity are the most important [6][7][8][9][10][11]. An alternative is welcome, and recent studies suggest a positive effect of MMF in children with nephrotic syndrome of various etiologies [12][13][14][15][16][17][18][19][20][21]. Here we report the first randomized controlled trial comparing the side effects and efficacy of MMF and CsA in children with frequently relapsing nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The results from several uncontrolled studies have recently suggested a positive effect of the relatively new immunosuppressive drug mycophenolate mofetil (MMF) in preventing relapses in children with frequently relapsing nephrotic syndrome due to minimal changes and various other nephropathies [12][13][14][15][16][17][18][19][20][21]. Mycophenolate mofetil inhibits inosine monophosphate dehydrogenase, an enzyme required for the de novo pathway of purine synthesis which, in turn, is essential for the proliferation of B and T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…19 Taken together, our data as well as recent pharmacokinetic studies confirm the value of therapeutic drug monitoring accompanying MMF therapy in patients with the nephrotic syndrome. 13,21 To estimate the effect of MPA exposure, we compared relapse rates in patients with low and high MPA exposure in a post hoc analysis. MPA exposure was strongly associated with therapeutic efficacy, as confirmed by ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies with limited statistical power have shown that MMF has steroid-sparing effects and reduces relapse rates in patients with FR-SSNS, albeit with varying efficacy. [11][12][13][14][15][16][17][18] We studied efficacy and safety of MMF in patients with FR-SSNS in comparison with CsA in a prospective randomized multicenter open-label crossover trial.…”
mentioning
confidence: 99%
“…Mycophenolate mofetil (MMF) is an immunosuppressive agent more recently added to the therapeutic armamentarium against steroid resistant (SRNS), frequently relapsing (FRNS) and steroid or cyclosporine dependent nephrotic syndrome (SDNS, CsADNS) (1)(2)(3)(4)(5)(6)(7). It has emerged as a new agent without nephrotoxicity and gonadal toxicity (3).…”
Section: Introductionmentioning
confidence: 99%